Antimicrobial Stewardship Training for Infectious Diseases Fellows: Program Directors Identify a Curriculum Need. (16th April 2018) - Luther, Vera P; Shnekendorf, Rachel; Abbo, Lilian M; Advani, Sonali; Armstrong, Wendy S; Barsoumian, Alice E; Beeler, Cole B; Bystritsky, Rachel; Cherabuddi, Kartikeya; Cohen, Seth; Hamilton, Keith W; Ince, Dilek; et al.
Abstract: A needs assessment survey of infectious diseases (ID) training program directors identified gaps in educational resources for training and evaluating ID fellows in antimicrobial stewardship. An Infectious Diseases Society of America–sponsored core curriculum was developed to address that need.